Evaluasi Kebijakan Tugas Pokok Dan Fungsi Bagian Protokol Sekretariat Daerah Kabupaten Pandeglang - Muhammad Imam Murad (HK Publishing, 2025)
The government has made various efforts to produce faster, more accurate, and transparent services. One element in the regional government organization is the protocol. The main tasks and functions that can make an activity run well, the formulation of the problem in this study is how to evaluate the policy of the main tasks and functions of the protocol section of the Pandeglang Regency Regional Secretariat. The purpose of this study is to analyze the main tasks and functions of the protocol section of the Pandeglang Regency Regional Secretariat. Based on the indicators of Effectiveness, Efficiency, Adequacy, Equivalence, Responsiveness, and Accuracy. The type of research used in this study is descriptive qualitative. The number of research informants is 8 people with data collection techniques through interviews and analysis with qualitative methods as research procedures that produce descriptive data. The results of the evaluation of the policy of the main tasks and functions can be concluded as not yet good and must be improved in the distribution of assignment schedules to protocol staff in an activity, especially in the indicators of Equivalence and Accuracy. In addition, the protocol section has not been able to organize unannounced official visits or receive and welcome guests who visit suddenly, causing protocol staff to appear unprofessional and lack coordination in prioritizing public service activities. Limited use of facilities, including official vehicles, is an indicator that hinders the performance of protocol officers in carrying out their primary duties and functions. This results in assigned personnel not meeting field needs and also limits the protocol's mobility. Therefore, additional budget and official vehicles are needed to strengthen performance and support the protocol's primary duties and functions in facilitating leadership activities. Keywords : Protocol, Task, Main, Function, Leadership.